Whistleblowing System dan Pencegahan Fraud: Sebuah Tinjauan Literatur - Benny Marciano; Ardiansyah Syam; Suyanto Suyanto; Nurmala Ahmar (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2021)
This study aims to examine previous research literature on the effect of the whistleblowing system as a collaborative system on fraud prevention in a company or organization. This study uses a review of various literature on fraud prevention available in various databases. The results of this study indicate that the Whistleblowing System (WBS) is a form of illegal act reporting and supervision of an organization or company. There are 4 (four) important elements in the WBS, namely anonymity, independence, accessibility and follow-up. WBS is an effective mechanism in preventing fraud and in its implementation requires the company's commitment to protecting the whistleblower's personal data, a clear and responsible reporting mechanism and the process of evaluating and improving the system. Therefore, to support fraud prevention, companies are advised to implement an effective Whistleblowing system.